Search for supersymmetry in proton-proton collisions at 13 TeV using identified top quarks - Sirunyan, A. M. (2018)
A search for supersymmetry is presented based on proton-proton collision events containing identified hadronically decaying top quarks, no leptons, and an imbalance p(T)(miss) in transverse momentum. The data were collected with the CMS detector at the CERN LHC at a center-of-mass energy of 13 TeV, and correspond to an integrated luminosity of 35.9 fb(-1). Search regions are defined in terms of the multiplicity of bottom quark jet and top quark candidates, the p(T)(miss) , the scalar sum of jet transverse momenta, and themT2 mass variable. No statistically significant excess of events is observed relative to the expectation from the standard model. Lower limits on the masses of supersymmetric particles are determined at 95% confidence level in the context of simplified models with top quark production. For a model with direct top squark pair production followed by the decay of each top squark to a top quark and a neutralino, top squark masses up to 1020 GeVand neutralino masses up to 430 GeVare excluded. For amodel with pair production of gluinos followed by the decay of each gluino to a top quark-antiquark pair and a neutralino, gluino masses up to 2040 GeVand neutralino masses up to 1150 GeVare excluded. These limits extend previous results.